PENINGKATAN KAPASITAS PENGRAJIN CENGKEH DALAM PENDAMPINGAN AKUNTANSI DAN PENGOLAHAN PRODUK TEH CELUP DI DESA SUKABARES KECAMATAN CIOMAS, SERANG - Afriani, Raden Irna; Handayani, ⁠Novi; Patia, ⁠Gina; ⁠Iqbal, ⁠Iqbal; Safara, ⁠Fajarwati; Umam, ⁠Gausul; Surachman, Alif; Khofiyah, ⁠Uswatun (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2024)
This community service activity aims to increase the capacity of clove craftsmen in Sukabares Village, Ciomas Regency, through assistance with accounting and processing of tea bag products. Implemented on July 30 2024, this program involves 30 local clove craftsmen. The methods used include digital accounting training, clove tea bag processing workshops, and digital marketing training. Results showed a significant increase in accounting understanding, with 85% of participants able to prepare simple financial reports post-training. In the aspect of product diversification, 90% of participants succeeded in making a prototype of clove tea bags that met market quality standards. Digital marketing adoption increased from 10% to 70% of participants. The formation of the Joint Business Group (KUB) "Cengkeh Makmur Sukabares" was a significant indirect result. The main challenges include limited internet access and the availability of quality raw materials. This program not only increases the technical capacity of craftsmen but also opens up insight into wider business development potential. Continuous mentoring and collaboration with various stakeholders is recommended to ensure the long-term impact of this initiative